Internationalization Process of Bunkering Companies: a Case Study of OW Bunker Lithuania - Gavrilov, Sergej (2012)
Even though that the significance of the international service companies in the global economy increases every year, there is little knowledge on the internationalization process of the service companies, especially on the bunkering companies. This research paper discusses findings of exploratory and descriptive case study of internationalization process of the OW Bunker Company. The combination of Uppsala model and network theory is used as theoretical platform for the case study. The findings of the study suggest that Uppsala model and network theory can explain the internationalization process of the bunkering company. The case of OW Bunker support the notions of Uppsala model – psychic distance and partly establishment chain – and premises of network theory – the internationalization path, network position and motives to internationalize. Apart from the classical expressions of learning under the Uppsala model, there is an alternative learning, which heavily relies on the network relations.